Students' Perceptions of the E-Module in Mathematics and Physics Based on Gender Differences - Astalini, Astalini; Darmaji, Darmaji; Kurniawan, Dwi Agus; Ramadhanti, Auliya (Journal of Education Reseach and Evaluation, 2021)
The lack of quality learning materials will automatically affect the effectiveness and success of learning. This study analyses the differences in students' perceptions of the e-module product Mathematics I vector material based on gender differences. This type of research is quantitative research with descriptive statistical analysis techniques and inferential analysis. The research sample amounted to 90 students using simple random. Data analysis was descriptively carried out using normality, homogeneity, and ANOVA tests where the significance was more than or equal to 0.05. The results of the ANOVA test showed that there were differences in perception. Based on gender with a significance value of 0.037 in women and 0.022 in men. Furthermore, in the post hoc test or further test Gabriel showed that in class A and B with a significance of 0.047 for the female gender. Meanwhile, the male gender in class A and class C had a significant difference with a significance value of 0.033. Compared to the male gender, women have more dominant differences caused by biological factors where women use their emotions more than men, whose more realistic thinking is better. The use of the Mathematics e-module will significantly assist students in the teaching and learning process to make it easier to understand and seem interesting. Knowing how the differences and diversity of perceptions of the developed e-modules will certainly help educators make teaching materials that are appropriate and able to attract students' interest.